ЛЮДСЬКИЙ КАПІТАЛ ЯК НЕВІД’ЄМНИЙ ЧИННИК СОЦІАЛЬНО-ЕКОНОМІЧНОГО РОЗВИТКУ - Lopatynskyi, Yurii; Kobelia, Zoriana; Sheliuzhak, Ivanna (Чернівецький національний університет імені Юрія Федьковича, 2020)
Досліджено людський капітал у категоріально-структурному аспекті та макрорівні через індекс людського розвитку в Україні та Польщі. Зменшення індексу пов’язане з пандемією коронавірусу, що спричинило економічний спад у багатьох країнах світу. Окреслено переваги та недоліки для інвесторів, які хочуть вкладати кошти в розвиток окремого робітника чи групи працівників. Серед переваг виділено поліпшення надання якості послуг, зростання продуктивності праці та фінансових результатів, формування стійкого соціально-психологічного клімату в колективі. Серед основних недоліків формування людського капіталу виявлено фінансовий ризик і втрачений час, можлива недоброчесність з боку працівника, невизначений результат. Увага акцентується на тому, що людський капітал є невід’ємною складовою загальнодержавного розвитку й ефективної кадрової політики організації.
HUMAN CAPITAL AS AN INTEGRAL FACTOR OF SOCIAL AND ECONOMIC DEVELOPMENT
The article examines human capital in the categorical and structural aspect, identifies the main features of long-term investment in human capital, which can recoup the costs of the enterprise and significantly improve the financial and economic performance of the organization as a whole in the future. It is emphasized that the employee is not an expense of the enterprise, but a strategic resource of the company. The purpose of the article is to define human capital as an integral factor of socio-economic development of the state, enterprise, institution, organization, as well as to outline the pros and cons of investing in human capital. The advantages and disadvantages for investors who want to invest in the development of an individual worker or group of workers are identified. Among the advantages are the improvement of service quality, productivity growth and financial indicators, the formation of a stable socio-psychological climate in the team, and the involvement of highly qualified workers. Among the main disadvantages of investing in human capital are financial risk and lost time, possible dishonesty on the part of the employee, uncertain outcome. Human capital at the macro level is studied through the human development index in Ukraine and Poland. The decline in the index is due to the coronavirus pandemic, which has caused an economic downturn in many countries around the world. Emphasis is placed on the fact that human capital is an integral part of national development and effective personnel policy of the organization. A modern manager must consider his subordinates as an untapped potential of the organization that needs to be developed. The skills and abilities of employees "wear out" quickly, as changes in the external environment change and displace those people who do not want to adapt to modern conditions of existence and development.
Keywords: людський капітал, індекс людського розвитку, інвестиції, розвиток персоналу, підвищення кваліфікації; human capital, human development index, investments, personnel development, advanced training.